PENGARUH BRAND EXTENSION PEMBERSIH WAJAH POND’S WHITE BEAUTY KE PELEMBAB WAJAH POND’S FLAWLESS WHITE TERHADAP KEPUTUSAN MEMBELI KONSUMEN DI FAKULTAS EKONOMI USU - Arlina Nurbaity Lubis Lubis; sri lastri sitompul sitompul (Jurnal Media Informasi Manajemen, 2013)
Brand extension is the strategy used Pond’s to obtain greater market segment. Based on the temporary observation conducted randomly to 20 respondents on students Economy USU, 14 of them claimed to use cleaning products facial Pond’s White Beauty and facial moisturizer Pond’s Flawless White so that researchers have an interests in doing research on the effect of brand extension on buying decisions of consumers in the Faculty USU Economics. The purpose of this study was to identify and analyze the influence of Brand Extension Cleanser to Pond’s White Beauty Face Moisturizer Pond’s Flawless White Against Consumer Buying Decisions in the Faculty of Economics USU. This researchis associative, because the researchers wanted to know how the effect of Brand Extension Cleanser to Pond's White Beauty Face Moisturizer Pond's Flawless White Against Consumer Buying Decisions in the Faculty of Economics USU. Primary data were collected through questionnaires distributed to students in the Faculty of Economics USU using facial cleanser Pond's White Beauty and facial moisturizer Pond's Flawless White with sample were 94 respondents. Hypotesis testing using simple regression analysis, the coefficient of determination and test-t. The results obtained showed that the facial cleanser Brand extension Pond's White Beauty to facial moisturizer Pond's Flawless White has positive and significant impact on consumer buying decisions at the Faculty of Economics USU. Determinant coefficient of 0.595 means the ability of brand extension products facial cleansers Pond's White Beauty to facial moisturizer Pond's Flawless White in explaining consumer buying decisions at the Faculty of Economics USU 59.5% while the remaining 40.5% is influenced by factors - other factors that are not included in the model equations.